FACTORS THAT AFFECT CUSTOMER SATISFACTION IN ONLINE SHOPPING FOR MULTIVITAMIN SUPPLEMENT DURING PANDEMIC OF COVID-19 IN INDONESIA - Primaturia, Cory; Berlianto, Margaretha Pink (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2022)
The online purchase of multivitamins during the COVID-19 pandemic has increased significantly because of not only the fact that until now there is no specific treatment for the infection but also the fear of being infected. Purpose - This study aims to investigate the direct influence of determinant factors of customer satisfaction, and the mediating factors of customer satisfaction and fear of COVID-19 in increasing repurchase intentions during the pandemic on multivitamin and micronutrient. Design/Methodology/Approach - This study used quantitative research and data collection was collected using questionnaire. The target population of this research were people that have purchased online multivitamin in e- commerce in Indonesia during pandemic COVID-19. The number of samples were determined to be which 235 samples. The sampling technique use was purposive sampling. Partial Least Square-Structural Equation modelling (SEM-PLS) is applied to this study. Findings - The study result indicated that the repurchase intention was positively affected by customer satisfaction that effected by site design, product price, time saving, product information linked to customer satisfaction and directly influenced by the fear of COVID-19. Research Limitation/Implication - This study only focuses on security, site design, product prices, product quality, product delivery, time, and product information. There are still many other variables that can affect consumer satisfaction in influencing repurchase intention. Practical implication - This study suggests that to retain repurchase intention during this pandemic, practitioner of m-commerce should increase their customer satisfaction by improving the determinant factors of e-commerce and taking emotional factor into consideration.Original/value - This journal provides input for online shopping platform management to pay more attention to factors that are important to be maintained and improved in order to increase consumer satisfaction which will positively affect repurchase intention.